Chemokine Profiles Are Affected in Serum of Patients with Acute Rejection of Kidney Allograft - Lenka Krupickova; Martina Fialova; Marek Novotny; Veronika Svachova; Kristyna Mezerova; Eva Cecrdlova; Ondrej Viklicky; Ilja Striz (Mediators of Inflammation)
Kidney allograft transplantation improved the prognosis and quality of life of patients with end-stage renal diseases but the occurrence of acute rejection represents a limitation of the final outcome. Noninvasive biomarkers are needed as well as further advancements in the understanding of immune mechanisms of reaction to the allograft. Our study of 138 patients focused on one-year monitoring of serum concentrations of 12 chemokines regulating the recruitment of different immune cells into transplanted allograft and on in vitro regulation of the same chemokines release by interactions of renal proximal epithelial cells with monocyte/macrophage cell line stimulated with TNF alpha. In a group of 44 patients with acute rejection, higher serum pretransplant levels of CXCL1, CXCL5, CXCL6, CCL2, CCL21, and particularly CXCL10 and CX3CL1(both p<0.001) were found suggesting their higher proinflammatory status as compared to subjects with the uncomplicated outcome. In samples collected at the day of biopsy positive for acute rejection, chemokines CXCL9 and CXCL11 attracting preferentially Th1 lymphocytes were found to be upregulated. In our in vitro model with TNF alpha induction, renal proximal epithelial cells seemed to be a more potent source of chemokines attracting neutrophils as compared to monocyte/macrophage cell line but the coculture of these cells potentiated release of neutrophilic chemokines CXCL5 and CXCL6. Similar augmentation of chemokine production was found also in the case of CCL2. On the other hand, adding of monocytes/macrophages to a culture of renal epithelial cells suppressed the release of CXCL10 and CXCL11 attracting T lymphocytes. We assume from our data that in kidney allograft transplantation, chemokines attracting neutrophils, T lymphocytes, and monocytes are induced simultaneously and measurement some of them in combination might be used as biomarkers of acute rejection. Mutual cell-cell interactions of immune cells with renal parenchyma seem to be important for fine regulation of chemokine release.